Lucius C. Dunn papers - Dunn, Lucius C. (Lucius Claude), 1885-1963.
Correspondence, memoranda, journal, writings, memoirs, lectures, research notes, musical compositions, official orders, reports, schedules, clippings, scrapbooks, printed matter, prints, slides, photographs, and other papers pertaining to Dunn's career in the U.S. Navy and to his writings and research projects particularly in the field of naval history.
Documents his naval service during and after World War I in Europe and the Pacific Ocean, his command of the destroyers McFarland and Pillsbury and of the river gunboat Mindanao, and his service as assistant to Admiral Albert P. Niblack. Subjects include China and the Japanese occupation of Shanghai in 1932, the Chinese Communist party (Zhongguo gong chan dang), postwar Europe, and Nicaragua. Correspondents include Jeff Busby, John B. Earle, William S. Hill, Harry M.P. Huse, and Albert P. Niblack.
Naval officer and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Busby, Jeff -- Correspondence; Earle, John B. -- 1885- -- Correspondence; Hill, William S. -- Correspondence; Huse, Harry M. P. -- 1858-1942 -- Correspondence; Niblack, Albert P. -- 1859-1929.; Niblack, Albert P. -- 1859-1929 -- Correspondence; United States. -- Navy; United States. -- Navy -- Foreign service -- Europe; United States. -- Navy -- Foreign service -- Pacific Area; McFarland (Destroyer : DD-237); Mindanao (Gunboat : PR-8); Pillsbury (Destroyer : DD-227); Zhongguo gong chan dang; Naval history; Reconstruction (1914-1939) -- Europe; Storage batteries; World War, 1914-1918 -- Naval operations, American; China; Nicaragua; Shanghai (China) -- History -- Japanese Invasion, 1932.; United States -- History, Naval; Authors; Naval officers